Concentration of some Heavy Elements in Water , Sediment and Plants in Al-Gharraf River in Thi-Qar Province –South of Iraq - Ali S. Ali; Basim Y. Al-Khafaji; Haider R. Al-Gezi (University of Thi-Qar Journal of Science, 2020)
The present study was included to estimate the Concentration and distribution of selected Heavy elements Cadmium, Lead, Nickel and Zinc from water, sediment and two species of plant ( Phragmites australis and Ceratophyllim demersum). Also same physical characteristic of this river in water , samples were collected of three stations in Al-Gharraf River in order to investigates the possibility of pollution in this area with these elements .three station (Al-Fajr districts , Qal’at Sukkar districts and Al-Rifa’I districts) were chosen to execute this study during the period from May 2018 until February 2019. And the high temperature was recorded (13 ٥C in winter to 30 ٥C in summer), pH (7.44 to 7.8) and Turbidity (2.41 to 10.2)NTU. and salinity (0.01 to 0.069) ppt. Also all the heavy metals recorded a significant increase in water and Ceratophyllin demersum plant samples in the winter higher than summer and in the sediments and Phragmites australis plant the rise in the winter was only in the elements nickel and zinc, but in cadmium and lead were concentration low or do not make a big difference in the winter compared to the summer , Where the highest percentage of nickel and zinc in the sediments in the second and third stations respectively reached 86.2 mg / kg dry weight . The lowest concentration of cadmium concentration in water samples at the first station for the summer was 0.0021 mg / L . Where there is a positive relationship between the increase in concentrations.